DIAGNOSIS OF THE PLANT BIODIVERSITY OF AN ANTHROPOGENIC ZONE IN ALGIERS: CASE OF THE BOUZARÉAH FOREST MASSIF - Safia Abla 1*, Mohammed Djebbouri3, Sabrina Kefil 1, 2 (Chelonian Research Foundation, 2024)
The flora of peri-urban forests is usually understudied compared to other forest types. This flora harbors a plant biodiversity that deserves better understanding. The Bouzaréah forest massif is a geographical area that boasts high biological diversity. It possesses a rich and diverse flora, the characteristics of which need to be determined for sustainable management. Over the decades, this area has experienced continual regression, mainly due to a combined action of climatic, ecological, and anthropogenic factors. 65 phytosociological surveys were conducted in the study area. Plant groups were determined using a modified TWINSPAN classification. For each vegetation group, diagnostic species were selected based on their fidelity index (phi coefficient). We identified 7 plant groups and selected 69 diagnostic species. Results obtained and verified through field investigations show that group 5, a shrubland located on the north-facing slope where conditions are favorable, is the richest and most diversified in plant species compared to other groups. Given the alarming degradation of ecosystems by humans and the current context of climate change, understanding the floristic diversity, structure, and characteristics of different floristic groups is crucial for effective management of urban forest spaces. KEY WORDS: -Structure, Forest formations, Bouzaréah forest massif, Algeria.